2016
DOI: 10.1002/mds.26762
|View full text |Cite
|
Sign up to set email alerts
|

Freezing/festination during motor tasks in early-stage Parkinson's disease: A prospective study

Abstract: Freezing and festination of the upper and lower limbs are observed soon after the diagnosis of PD and may be early biomarkers for disease progression. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 52 publications
(68 reference statements)
4
36
2
Order By: Relevance
“…Furthermore, the potential role of anxiety during the metronome condition should not be overlooked since it is highly prevalent in freezers [ 41 ] and can lead to freezing [ 42 ]. In the present study, the single imposed frequency (4 Hz, previously demonstrated to trigger freezing [ 30 ]) was higher than the patient’s self-generated frequency. Auditory cueing appears to increase the priority given to maintaining frequency because the amplitude decreased for the feet (but not for the hands).…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Furthermore, the potential role of anxiety during the metronome condition should not be overlooked since it is highly prevalent in freezers [ 41 ] and can lead to freezing [ 42 ]. In the present study, the single imposed frequency (4 Hz, previously demonstrated to trigger freezing [ 30 ]) was higher than the patient’s self-generated frequency. Auditory cueing appears to increase the priority given to maintaining frequency because the amplitude decreased for the feet (but not for the hands).…”
Section: Discussioncontrasting
confidence: 49%
“…severe hypokinesia) for at least 0.5 s; this might not be totally specific for freezing phenomena. In the absence of PD, freezing episodes of the upper or lower limbs are rarely observed in elderly patients [ 30 ]. However, this does not explain the differences observed when comparing upper limb and lower limb effectors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations